2012
DOI: 10.1074/jbc.m111.337493
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Levels Regulated by Carnitine Palmitoyltransferase 1C Control Dendritic Spine Maturation and Cognition

Abstract: Background: CPT1C is highly expressed in hippocampus, but its cellular and physiological function is unknown. Results: CPT1C overexpression increases ceramide levels, and CPT1C deficiency impairs dendritic spine morphology and spatial learning. Conclusion: Regulation of ceramide levels by CPT1C is necessary for proper spine maturation. Significance: We describe a new function of CPT1C in cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 26 publications
1
102
0
Order By: Relevance
“…9,22 CPT1C has been recently demonstrated to be expressed in pyramidal neurons of hippocampus and is located in the ER. Sierra et al 14 demonstrated that CPT1C possessed CPT activity, while Carrasco et al 23 indicated that CPT1C may regulate ceramide levels in neurons. Nevertheless, it has been reported that CPT1C conserves the affinity for Malonyl-CoA, which inhibits all the CPT1 family members.…”
Section: Discussionmentioning
confidence: 99%
“…9,22 CPT1C has been recently demonstrated to be expressed in pyramidal neurons of hippocampus and is located in the ER. Sierra et al 14 demonstrated that CPT1C possessed CPT activity, while Carrasco et al 23 indicated that CPT1C may regulate ceramide levels in neurons. Nevertheless, it has been reported that CPT1C conserves the affinity for Malonyl-CoA, which inhibits all the CPT1 family members.…”
Section: Discussionmentioning
confidence: 99%
“…When ceramide levels were analyzed in various regions of the brain (hippocampus, motor cortex, cerebellum, and striatum), the content of the most abundant ceramide in brain (C18:0), and its derivative sphingosine was lowered in fasted CPT1C KO mice [30,47]. Moreover, overexpression of CPT1C in the arcuate (Arc) nucleus increased ceramide levels in this nucleus, while CPT1C KO mice did not show the expected increase in ceramide in response to fasting or to ghrelin treatment.…”
Section: Metabolism Of Ceramidesmentioning
confidence: 99%
“…To confirm that CPT1C-induced ceramide modulation occurs in neurons and not in other brain cells, an in vitro model of pure neurons was used in following experiments [47]. CPT1C overexpression in cultured hippocampal neurons increased ceramide almost two-fold, while cultured neurons from CPT1C KO mice showed a notable reduction.…”
Section: Metabolism Of Ceramidesmentioning
confidence: 99%
See 2 more Smart Citations